Model and Practice of Strategic Policy Process in Indonesia: Case Study in Indonesian Central Government - Achmad Nurmandi; Mohammad Jafar Loilatu (New Innovations in Economics, Business and Management Vol. 6, 2022)
Since 1998, the Indonesian government has implemented a Strategic Management approach under Government Regulation No. 108/200; however, the government has not evaluated the strategy’s effectiveness. However, in 2009, President Yudhoyono’s administration introduced a new approach known as Rencana Pembangunan Jangka Menengah (RPJMD) – Medium Term Development Planning. An intriguing question concerns the government’s compliance with this strategic plan. To put it another way, is the strategic plan being implemented? In this paper, both authors investigate their experiences with attempting to introduce the Strategic Management model and practise in the Indonesian public sector, focusing on process and tools. The casual loop model of the system dynamics method was used in this research, which is historical and descriptive. According to the study, the government’s strategic planning model was a linear process model linked to critical success factors such as leadership, professional coordination among governmental units, and monitoring of the entire process and its instruments: planning, implementation, and evaluation.